Strategi Pemasaran Pendidikan Melalui Kelas Unggulan Teknologi Informasi di Ma YPK Cijulang - Iip Mustopa Syaripah (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2025)
The main objective of this research is to determine A The marketing strategy for education through superior    IT classes at MA YPK Cijulang. The results of this research show that based on the information technology-based marketing mix concept at MA YPK Cijulang, which is explained in terms of product content or superiority, information technology-based marketing methods and media have attracted people to become their school of choice. The school principal has made maximum efforts to involve teachers and employees in information technology-based marketing. Supporting factors are the use of the internet in marketing education through predetermined applications, students who excel, the use of print media such as billboards, pamphlets and brochures, fees and free school uniforms, curriculum, school accreditation, achievements, extracurriculars. The inhibiting factors are the large number of competition between schools, facilities and infrastructure is very less compared to state-based schools.